Social representations of men and women in relation to gender violence in Apartadó, Colombia - Marcela María Morales Córdoba (Senderos Pedagogicos, 2023)
This article is the result of a qualitative research with a descriptive phenomenological design, whose main objective was to analyze the social representations of gender and gender violence held by men and women. The techniques used to obtain the information were semi-structured interviews and indirect observation. The results are based on the description of experiences, meanings, expressions and subjectivities of gender, of the female-male stereotypes, the female-male conception, in addition to the discourses that explain that gender violence is experiential and that those affected are women and members of the LGBTIQ community. Similarly, men are made visible as victims. This study concludes that the media are effective instruments for generating knowledge about gender issues and gender-based violence; however, they can be a medium in which the perpetuation and consummation of violence is promoted.